High-throughput assays to identify archaea-targeting nitrification inhibitors - Beeckman, Fabian; Drozdzecki, Andrzej; De Knijf, Alexa; Audenaert, Dominique; Beeckman, Tom; Motte, Hans (Frontiers in Plant Science, 2024)
Nitrification is a microbial process that converts ammonia (NH3) to nitrite (NO2-) and then to nitrate (NO3-). The first and rate-limiting step in nitrification is ammonia oxidation, which is conducted by both bacteria and archaea. In agriculture, it is important to control this process as high nitrification rates result in NO3- leaching, reduced nitrogen (N) availability for the plants and environmental problems such as eutrophication and greenhouse gas emissions. Nitrification inhibitors can be used to block nitrification, and as such reduce N pollution and improve fertilizer use efficiency (FUE) in agriculture. Currently applied inhibitors target the bacteria, and do not block nitrification by ammonia-oxidizing archaea (AOA). While it was long believed that nitrification in agroecosystems was primarily driven by bacteria, recent research has unveiled potential significant contributions from ammonia-oxidizing archaea (AOA), especially when bacterial activity is inhibited. Hence, there is also a need for AOA-targeting nitrification inhibitors. However, to date, almost no AOA-targeting inhibitors are described. Furthermore, AOA are difficult to handle, hindering their use to test or identify possible AOA-targeting nitrification inhibitors. To address the need for AOA-targeting nitrification inhibitors, we developed two miniaturized nitrification inhibition assays using an AOA-enriched nitrifying community or the AOA Nitrosospaera viennensis. These assays enable high-throughput testing of candidate AOA inhibitors. We here present detailed guidelines on the protocols and illustrate their use with some examples. We believe that these assays can contribute to the discovery of future AOA-targeting nitrification inhibitors, which could complement the currently applied inhibitors to increase nitrification inhibition efficiency in the field and as such contribute to a more sustainable agriculture.